Come back when you're infected: pharmacy access to sterile syringes in an Arizona Secret Shopper Study, 2023 - Danielle M. Russell; Beth E. Meyerson; Arlene N. Mahoney; Irene Garnett; Chris Ferrell; Kylee Newgass; Jon D. Agley; Richard A. Crosby; Keith G. Bentele; Nina Vadiei; David Frank; Linnea B. Linde-Krieger (BMC, 2024)
Abstract Background Pharmacies are critical healthcare partners in community efforts to eliminate bloodborne illnesses. Pharmacy sale of sterile syringes is central to this effort. Methods A mixed methods "secret shopper" syringe purchase study was conducted in the fall of 2022 with 38 community pharmacies in Maricopa and Pima Counties, Arizona. Pharmacies were geomapped to within 2 miles of areas identified as having a potentially high volume of illicit drug commerce. Daytime venue sampling was used whereby separate investigators with lived/living drug use experience attempted to purchase syringes without a prescription. Investigator response when prompted for purchase rationale was "to protect myself from HIV and hepatitis C." A 24-item instrument measured sales outcome, pharmacy staff interaction (hostile/neutral/friendly), and the buyer's subjective experience. Results Only 24.6% (n = 28) of 114 purchase attempts across the 38 pharmacies resulted in syringe sale. Less than one quarter (21.1%) of pharmacies always sold, while 44.7% never sold. Independent and food store pharmacies tended not to sell syringes. There emerged distinct pharmacy staff interactions characterized by body language, customer query, normalization or othering response, response to purchase request and closure. Pharmacy discretion and pharmacy policy not to sell syringes without a prescription limited sterile syringe access. Investigators reported frequent and adverse emotional impact due to pharmacy staff negative and stigmatizing interactions. Conclusions Pharmacies miss opportunities to advance efforts to eliminate bloodborne infections by stringent no-sale policy and discretion about syringe sale. State regulatory policy facilitating pharmacy syringe sales, limiting pharmacist discretion for syringe sales, and targeting pharmacy-staff level education may help advance the achievement of public health goals to eliminate bloodborne infections in Arizona.